Serum Calcium And Phosphateleveelsin Patients With Chronic Myeloid Leukemia Taking Different Dose of Tyrosine Kinase Inhibitors - Bassam Francis Matti; Shahla'a Fadhil Sabir; Maysaa Ali Abdul Khaleq; Marwah Hasan Al kaabi (College of Pharmacy / Mustansiriyah University, 2018)
Objective: chronic myeloid leukemia (CML) is a myeloproliferative confusion characterized by the occurrence of an acquired mutation which affect the hematopoietic stem cell, treatment of CML with tyrosine kinase inhibitors (TKI) has resulted in high response rates compared to the interferon alpha and hydroxy urea. However, the long-term consequences of TKI had an effect on calcium (Ca++ ) and phosphate(PO4-2 ) levels which may have adverse events on the cardiac and skeletomuscular contraction. Methods:  in a cross-sectional study, 95 patients with CML receiving different TKI treatment for at least one year duration were randomly divided in to three groups: group (1) who received imatinib myselate (Gleevec) 400mgper oral per day,the second group were patients received gleevec 600mg-800mg/day, while the third group patients were received nilotinib 800mg/day as a second line therapy after failure to imatinib mylselate response . Results: in the present study,serum Ca++  level was a significant lower statistical different with p < 0.05 when compared with serum level of PO4-2inpatients treated with imatinib and nilotinib with lower serumCa++ and PO4-2levelsin imatinibpatientsgroup than patientsused nilotinib group with p-value 0.049 and 0.005 subsequently. Conclusion:  imatinib therapy with the long term use may cause hypocalcemia and hypophospatemia without significant correlation more than treatment with nilotinib where  significant correlation was between serum Ca++ and PO4-2and these changes may give an idea that disturbance of serum Ca++, PO4-2was multifactorial